A Novel ID-Based Authentication and Key Exchange Protocol Resistant to Ephemeral-Secret-Leakage Attacks for Mobile Devices. (21st May 2015) - Tseng, Yuh-Min; Huang, Sen-Shan; Tsai, Tung-Tso; Tseng, Li
With the rapid development in wireless communications and cloud computing technologies, clients (users) often use handheld mobile devices to access remote servers via open network channels. To provide authentication and confidentiality between clients and servers, a large number of ID-based authentication and key exchange (ID-AKE) protocols have been proposed for mobile client-server environments. However, most of the existing ID-AKE protocols adopt the precomputation technique so that they become vulnerable to the ephemeral-secret-leakage (ESL) attacks, in the sense that an adversary could use the ephemeral secrets to reveal the private keys of clients from the corresponding exchange messages. In the paper, we propose a new ESL-secure ID-AKE protocol for mobile client-server environments. We formally prove that the proposed protocol satisfies the security requirements of both mutual authentication and key exchange while resisting the ESL attacks. When compared with previously proposed ID-AKE protocols, our protocol has higher security and retains computational performance, since it requires no bilinear pairing operation for mobile clients. Finally, we mention the possibility of adopting our protocol as an authentication method of the extensible authentication protocol (EAP) for wireless networks.